SISTEM PENDINGIN MENGGUNAKAN THERMO-ELECTRIC COOLER DENGAN KONTROLER PROPORTIONAL-INTEGRALDERIVATIVE - Indrawan, Wisnu; Suryono, Suryono (BERKALA FISIKA, 2019)
The cooling is one of the processes can be used for various types of applications, starting from maintaining food industry products and medical products such as drugs and vaccines. The cooling process now still uses compression-based preservation technology using cooling gas. The types of cooling gas used are R134a and R600a, however the R134a contains HFCs which has been banned for used and the R600a contains HF gas which can reduce the ozone layer. The current study designed hardware and software that is applied to thermoelectric coolers(TEC), i.e. it was designed a device used for the air conditioning system using a thermoelectric cooler with a Proportional Integral Derivative (PID) controller. This system used several tools such as temperature sensors, transistor with TIP31 type, bluetooth module, fan, and ATSAM3X8E microcontroller. In this study, temperature control was carried out based on the desired set-point temperature and temperature of the sensor. From this study, it can be found that the greater value of the voltage given, the greater the value of the Pulse Wave Modulation (PWM) will be produced. The higher value of PWM, the faster the temperature decreases in the cooler. From several tests, it can be concluded that the values of proportional control parameter (Kp) of 2.55, integral control parameter (Ki) of 100 and deferential controlparameter (Kd) of 200, more stable graph is obtained and close to the set-point value, with anerror value of 2.86%.Keywords : Cooling, thermoelectric, gas, controller, temperature